Effect of Intermittent normobaric hypoxia on sub maximal exercise performance at high altitude (3500 m) - Kaushik Halder; Anjana Pathak; Bhaumik G; Mantu Saha (Al Ameen Medical College, 2021)
Background: Intermittent hypoxic exposure (IHE) improves wellbeing and performance by modulating physiological processes. Though the effect of IHE on oxygen saturation (SpO2) and submaximal exercise performance (SEP) upon deployment of Indian military personnel at high altitude (HA) has not been studied yet. Objective: To observe the effect of IHE on SpO2and SEP among Indian military personnel at sea level (SL) and upon rapid induction to 3500 m altitude. The data obtained at HA were also compared with age and gender matched high altitude natives (HAN) and acclimatized lowlanders (ALR). Methods: Two hundred thirty three volunteers (age: 22 - 34 years) participated in the study. 210 participants were enrolled at SL and randomly divided into experimental (EXP) or control (CON) group. The EXP group were given IHE at 12% FIO2, 4 hrs. every day for 4 days at an altitude of 218 m. Both the groups were inducted to 3500 m by air. After IHE at SL and on day 7 at HA heart rate (HR), SpO2 and SEP were evaluated. 8 HAN and 15 ALR were also participated and their HR, SpO2 and SEP were evaluated at HA only. Results: At SL significant difference between CON and EXP group was noted in resting (HR) and during exercise and recovery (HR and SpO2; P<0.05). At HA, HR of CON group during exercise and recovery period was significantly higher than the other 3 groups (P<0.001). Resting SpO2 of EXP group was higher than other 3 groups but significant difference was noted with CON and HAN group (both P<0.001). During exercise and recovery at HA SpO2 of CON group was significantly lower than EXP group (P<0.001). Conclusion: Intermittent normobaric hypoxia exposure improves SpO2 and exercise performance during initial days of acclimatization at 3500 m altitude.